Effects of feeding cost effective total mixed ration using local ingredients on selected production and reproductive performances of Dorper sheep - Mira Panadi (2022)
The objectives of this study are to develop a total mixed ration (TMR) for Dorper sheep at different physiological statuses, i.e., lactating (Trial I), pre-weaning (Trial II) and post-weaning (Trial III). The effects of TMR were evaluated on feeding intake, nutrient intake, milk quality, body weight changes, body condition score (BCS), blood haematological parameters and nutrient digestibility. This research was conducted at Agropolitan Besut-Setiu, Terengganu, for 180 days feeding trial and seven (7) days digestibility trial. Twenty (20) lactating Dorper ewes (mean initial body weight: 50.89±2.19; 7 years old) in Trial I and twenty (20) Dorper lambs (mean initial body weight: 2.91±0.07 kg, 7 days old) in Trial II and Trial III were randomly assigned to four groups with five (5) sheep each, based on randomized complete block design (RCBD). In Trial I, control (CON 11) was fed with a basal diet consisted of Napier grass (Pennisetum purpureum) and commercial breeder pellet. The treatments consisted of lactating ration (LR), i.e., LR 9, LR 10 and LR 12, which contained ME varied at 11, 9, 10 and 12 for CON 11, LR 9, LR 10 and LR 12, respectively. In Trial II, pre-weaning lambs in control were fed with Napier grass (Pennisetum purpureum) and commercial creep pellet (CON 14), while treatments were fed with creep feed (CF) in the form of TMR, i.e., CF 16, CF 18 and CF 20. The lambs in all groups were fed with constant energy (11 MJ/kg DM ME) with varying CP (%) at 14, 16, 18 and 20 for CON 14, CF 16, CF 18 and CF 20, respectively. In Trial III, post-weaning lambs were fed with growing ration (GR) consisted of constant energy (11 MJ/kg DM ME) with varying CP (%) at 11, 14, 16 and 18 respectively for CON 11, GR 14, GR 16 and GR 18. The feeding intake of ewes and lambs was based on 4% and 3.5% of the body weight, respectively. Over 180 days of feeding trial (Trial I), there was a quadratic effect (p<0.05) of increased ME level on dry matter intake (DMI), nutrients intake and plateletcrit (PCT). The DMI (kg/d) of ewes in LR 9 (2.93) was significantly higher (p<0.05), followed by LR 10 (2.70), CON 11 (2.15) dan LR 12 (2.02). The ash (358.67 g/d), CP (415. 57 g/d) and crude fibre (CF) (947.27 g/d) intake in LR 9 was higher (p<0.05) compared to other groups. However, the PCT value of CON 11 (0.48%) was higher than LR 9 (0.22%). Besides, there was also a quadratic effect (p<0.05) on ether extract (EE) and CF digestibility when the ME level was increased. The EE digestibility (%) of those in LR 12 (95.67%) was higher (p<0.05) than those in LR 9 (88.55) and LR 10 (88.30), whereas CF digestibility (%) in CON 11 (70.30), LR 9 (77.85) and LR 10 (77.23) were significantly higher (p<0.05) than LR 12 (68.89). The milk fat (5.9%), lactose (1.66%), protein (7.1%), solids non-fat (10.5%), total solid (17.3%) and sucrose (0.27%) of LR 10 were notably higher (p<0.05) compared the other groups. The ewes in LR 10 (1.12 ng/ml) also had significantly higher (p<0.05) progesterone concentration, above 1 ng/ml at week 4 of the feeding trial. In trial II, the increased CP level from 14% to 20% resulted in a linear increase in DMI, nutrient intake, and ADG. The total DMI (kg/d) of pre-weaning lambs in CF 20 (1.06) was significantly higher (p<0.05) than CON 14 (0.61), but it did not differ significantly (p>0.05) with CF 16 (0.87) and CF 18 (0.68). Besides, the CP intake (g/d) of CF 20 (213.26) was higher (p<0.05), followed by CF 16 (140.16), CF 18 (123.63) and CON 14 (77.22). The EE intake (g/d) of CF 20 (41.76) also was significantly higher (p<0.05) than CON 14, but no significant difference (p>0.05) observed with CF 16 (58.60) and CF 18 (33.14). The ADG (g/d) of lambs in CF 18 (247.86) and CF 20 (251.28) were significantly higher (p<0.05) than CON 14 (196.58), but there was no obvious difference in the value (p>0.05) with CF 16 (217.95). Trial III also showed a linear effect (p<0.05) of varying CP levels on DMI, nutrient intake and digestibility. The DMI (kg/d) of post-weaning lambs in GR 18 (1.69) were higher (p<0.05) than CON 11 (1.19) and GR 14 (1.25). The CP intake (g/d) of GR 18 (297.05) was significantly higher (p<0.05) compared to other groups. The ADG (g/d) of GR 16 (105.88) was significantly higher (p<0.05), followed by GR 14 (72.94), GR 18 (69.41) and CON 11 (43.14). In term of cost effectiveness, the feeding cost/kg gain (RM/kg) of CF 18 (1.97) and CON 14 (1.63) were lower (p<0.05) than CF 16 (2.51) and CF 20 (3.35). Meanwhile, the cost of feed/kg gain (RM/kg) of GR 16 (8.94) was significantly lower (p<0.05) than CON 11 (22.92) and GR 18 (23.99). In conclusion, diets of lactating Dorper ewes consisted of 10 MJ/kg DM ME (LR 10) is adequate to enhance the DMI, nutrient intake and subsequently its lactating performances. For Dorper lambs, 16% CP and 14% CP in the diet are adequate to enhance pre- and post-weaning performances, respectively. However, by considering the benefit of feeding lambs, CF 18 (18% CP) and GR 16 (16% CP) are determined as the most cost-effective feed.